Implementation of Social Security Agency on Health (BPJS) Policy in Hospitals: A Systematic Review - Dwiyovita, Rizka; Etanaulia Marsim; Yessiana Luthfia Bahri (Universitas Muhammadiyah Surakarta, 2024)
Introduction: The Social Security Agency on Health (BPJS) is one of the health insurance providers that has been implemented in Indonesia, but so far the implementation of BPJS Health in Hospitals has still experienced obstacles in implementing the program. This study aims to analyze the implementation of BPJS Health policies in hospitals in more depth. The research aims to analyze the implementation of BPJS Health policies in hospitals in more depth. Method: This research is a systematic review. The article search using Google Scholar and PubMed databases used the keywords